Synthesis and Advanced Characterisation of Nanoparticle Gene Delivery Systems for mRNA therapeutics - Khosravi, Rahman (2025)
Nucleic acids, such as RNA and its derivatives, hold immense potential as therapeutic agents for treating a wide range of diseases, including genetic disorders, cancer, and infectious diseases. These molecules can regulate gene expression, silence pathological genes, or introduce therapeutic genes, offering highly specific and personalized treatment options. Despite these advantages, their clinical application is hindered by challenges such as poor stability, immunogenicity, and inefficient cellular uptake. Naked nucleic acids are rapidly degraded in biological fluids and cannot effectively penetrate cellular membranes due to their size and negative charge. Additionally, the immune system often identifies and eliminates carriers containing genetic drugs. To address these barriers, the development of effective delivery systems is critical. Lipid nanoparticles (LNPs), polymer-based carriers, and polymer-lipid hybrid nanoparticles (PLHNPs) have emerged as promising platforms for protecting nucleic acids from degradation, enhancing cellular uptake, and ensuring targeted delivery to specific tissues or cells. Among these, LNPs represent the most advanced non-viral delivery system, offering advantages in potency, payload, and design flexibility, but suffer from stability issues and potential immunogenicity. Polymeric nanoparticles, while stable and functional for controlled release, face challenges with regulatory acceptance. The integration of lipids and polymers into PLHNPs combines the strengths of both systems, providing enhanced biocompatibility, stability, improved payload capacity, controlled release, extended circulation time, and superior therapeutic efficacy. This thesis focuses on the development of novel PLHNPs, comparing their properties with conventional polymer- and lipid-based systems through various formulation and cell culture assays. These findings aim to advance the field of nucleic acid delivery and overcome key obstacles to the clinical translation of gene based therapies, particularly for challenging diseases like cancer.